Facilitating Language Growth for Children with Language Disorders: Can Teachers Act as Key Catalysts? - Virania Kusuma Dewi; Hery Setiyatna (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
Language development is an important aspect of early childhood education because it serves as a basis for communicating, thinking, and expressing oneself. However, not all children achieve optimal language development, some children experience language delays that can affect social, emotional, and academic abilities in the future. This study aims to describe the role of teachers in stimulating early childhood language development with language disorders in Bintang Kreasi early childhood education center. The research approach used is qualitative with a case study method. The data collection techniques in this study included observation, interviews, and documentation of classroom teachers and three children who showed symptoms of speech delay. The results of the study show that early childhood education center teachers in Bintang Kreasi have an important role as facilitators, language models, and emotional assistance for children with language disorders. The stimulation strategies carried out include interactive storytelling activities, singing, role-playing, and the use of media adapted to children's abilities. In addition, Bintang Kreasi early childhood education center teachers also apply a personal approach and gradual communication to foster children's confidence in speaking. In addition, collaboration between teachers, parents, and therapists is key in maintaining the consistency of stimulation at school and at home.